Student retention policies in public higher education in comparative perspective: Argentina, Brazil and Chile - Vargas, Hustana Maria; Heringer, Rosana (Education Policy Analysis Archives, 2017)
The higher education systems in Argentina, Brazil and Chile have considerable differences in relation to their origins and structures, but the elitist characteristic is a common feature of the three countries. There have been massification processes going on along the last three decades, supported by expansion of the system as well as by the adoption of affirmative action policies. Considering the multidimensional problems of student retention, given its financial, cultural, symbolic and psychological aspects, we are interested in analyzing, in a comparative perspective, the practices related to national/federal higher education students in these three countries. We have selected a few key categories for comparison, such as: 1) views about student retention in normative documents: Right? Assistance? 2) judicial and political nature of these actions: State commitment? Isolated actions? 3) institutional autonomy to design their own student retention models; 4) main student retention models found. Beyond the theoretical contributions, the analysis is based on national legislation about these issues, national level secondary data provided by educational agencies in each country and information provided by selected higher education institutions. This is mainly a descriptive effort, based on historical, legal and socioeconomic aspects, with the aim of giving an overview about the programs in different national contexts.